The United Nations Security Council and war - Vaughan Lowe (Oxford University Press, 2008)
This is the first major exploration of the United Nations Security Council's part in addressing the problem of war, both civil and international, since 1945. Both during and after the Cold War the Council has acted in a limited and selective manner, and its work has sometimes resulted in failure. It has not been--and was never equipped to be--the center of a comprehensive system of collective security. However, it remains the body charged with primary responsibility for international peace and security. It offers unique opportunities for international consultation and military collaboration, and for developing legal and normative frameworks. It has played a part in the reduction in the incidence of international war in the period since 1945